CRITICAL STUDY TO THE ENFORCEABILITY OF PASSIVE NATIONAL PRINCIPLE IN INDONESIA CRIMINAL CODE - Ridwan Ridwan (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Criminal law is law formulation to protect society and to establish society welfare as its address. Protection was, according criminal law, naturally as a concept of Human Rights protection. Based on those, therefore criminal law was implemented certainty, equality and expediency principle. But then, those law principles or basic values, seem difficult to improve by Indonesian citizen abroad, specifically Indonesian workers facing the law. Yet, according to limited-National Passive Principle in specific interest, and not including all Indonesian citizens abroad. It will cause unbalancing doelmatigheid ND rechtsmatigheid Principles not improving. Keywords: Principle, Protection, Concept.